KESALAHAN KLASIFIKASI BIAYA DAN DAMPAKNYA TERHADAP KEANDALAN LAPORAN KEUANGAN DI UMKM - Friesta Ayu Sanubari; Rita Yuniarti (Center for Economic Studies Universitas Katolik Parahyangan, 2026)
This research studies the impact of expense misclassification on the reliability of MSME X's financial statements located in Bandung. A noticeable phenomenon was that increased sales did not always increase net income. It was found later that this was due to the misclassification between expenses and assets. Knowing the importance of implementing proper accounting principles, especially for the recognition of expenses, so that financial statements can present the actual financial condition, becomes the basis for this study. Its novelty lies in the fact that little or no research with an exploratory approach has been done in this respect. The accounting record-keeping practice in MSMEs, despite being lesser-known, plays an important role in local economic matters. In this research, a qualitative approach with a purposive sampling technique was used, where data collection was carried out through in-depth interviews, observations, and analysis of MSME X's financial documents. The results show that wrong recognition of expenses, particularly fixed assets recorded as operating expenses, results in significant distortion in the income statement and lowers the reliability level of financial reports. Therefore, the outcome of this study reveals that improvement in accounting literacy, application of the Matching principle, and appropriate internal control are crucial for enhancing the quality of financial reporting by MSMEs. The findings provide practical suggestions that could be beneficial for practitioners to improve the practice of small businesses by enhancing accounting literacy and theoretical contributions toward strengthening the studies of financial accounting in micro and small entities.